An integrated bioinformatics platform for investigating the human E3 ubiquitin ligase-substrate interaction network - Yang Li (Nature Portfolio, 2017)
Protein stability modulation by E3 ubiquitin ligases is an important layer of functional regulation, but screening for E3 ligase-substrate interactions is time-consuming and costly. Here, the authors take an in silico naïve Bayesian classifier approach to integrate multiple lines of evidence for E3-substrate prediction, enabling prediction of the proteome-wide human E3 ligase interaction network.